2021
DOI: 10.3389/fpls.2021.644229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humic Acid Addition on Buffering Capacity and Nutrient Storage Capacity of Soilless Substrates

Abstract: Excessive application of fertilizers has become a major issue in croplands of intensive agricultural systems in China, resulting in severe non-point source pollution; thus, reduction in the use of chemical fertilizers has received significant attention. Improving the nutrient storage capacity of soils or substrates is an effective approach for solving this problem. Humic acids (HA) are excellent soil conditioners. Thus, in the present study, their ability to improve the physico-chemical properties of three sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 63 publications
(74 reference statements)
3
8
0
4
Order By: Relevance
“…We hypothesized that the long-term effect of digestate + biochar on nutrient mineralization would be negative, because of the tendency for biochar-mediated immobilization and sequestration. Both humic acids and biochar represent amendments that are rich sources of carbon and also act as nutrient storehouses [51][52][53][54]. However, biochar contains both labile (easily available) and recalcitrant carbon, leading to higher heterogeneity of organic matter in the digestate.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the long-term effect of digestate + biochar on nutrient mineralization would be negative, because of the tendency for biochar-mediated immobilization and sequestration. Both humic acids and biochar represent amendments that are rich sources of carbon and also act as nutrient storehouses [51][52][53][54]. However, biochar contains both labile (easily available) and recalcitrant carbon, leading to higher heterogeneity of organic matter in the digestate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the yield in CP 100% + HA was significantly higher than that in CP 100% in 2018. This is because the combination of CDAP and HA exerts beneficial effects on plant growth by improving the soil structure, fertility, and quality ( Calvo et al, 2014 ; Raiesi, 2021 ; Xu et al, 2021 ), and two consecutive years of application eventually resulted in significant changes. The combination of CDAP and HA provides an HA-incorporated enhanced-efficiency P fertilizer for environmentally friendly fertilization ( Figure 9 ), and future research should include P-inefficient crops (e.g., wheat).…”
Section: Discussionmentioning
confidence: 99%
“…HA consists of aromatic and aliphatic structures harboring various functional groups (mainly oxygen-containing), such as carboxyl (–COOH) and phenolic hydroxyl (–OH). Studies have shown that HA application reduced P fixation, improved the efficiency of low and high solubility P sources, increased P availability, and improved PUE ( Çimrin et al, 2010 ; Rosa et al, 2018 ; Shafi et al, 2020 ; Xu et al, 2021 ). HA improved soil structure by encouraging the formation of stable aggregates, which increased the productivity of soil crops ( Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations